Consumer attitudes and intentions to adopt smartphone apps: Case of business students - Masood ul Hassan; Rehana Kouser; Syed Shafqat Abbas; Muhammad Azeem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Increasing development in information communication technology led to huge attention over the mobile phones having extra features, normally referred as smartphones. Recently, the operating system and more importantly what distinguishes smartphones from ordinary phones, applications (Apps) had been given huge important in literature. We investigated the determinants behind the intention of using smartphone apps by choosing the perceived usefulness, perceived ease of use, social need, and perceived enjoyment as explanatory variables. We collected data from sample of 263 business students of Bahauddin Zakariya University of Multan (Pakistan) through the personally administered questionnaire. Factor analysis (based on Varimax rotation and Kaiser's normalization) was used. Relationship of interest was tested using the multiple linear regression analysis, three variables were found statistically significant but sufficient evidence was not found for the relationship of perceived enjoyment and intention to adopt apps. This study contributes to a more thorough understanding of the determinants of smartphones apps among business students by emphasizing the dimensions of perceived usefulness, perceived ease of use, social need and perceived enjoyment. Students' usage of smartphones apps is highly influenced by aspects of perceived usefulness, perceived ease of use, and social need. Smartphone application developers, and programmers should improve the current ability and contents to increase user enjoyment. Positive viral marketing spread via social networking sites could help application' developer providers to strengthen the competitive advantage of their product.
Keywords: 330; smartphones; apps; perceived usefulness; perceived enjoyment; social need; university graduates